From Play to Language: Infants' Actions on Objects Cascade to Word Learning. Issue 4 (17th July 2022) - Suarez‐Rivera, Catalina; Linn, Emily; Tamis‐LeMonda, Catherine S.
Abstract: Infants build knowledge by acting on the world. We conducted an ecologically grounded test of an embodied learning hypothesis: that infants' active engagement with objects in the home environment elicits caregiver naming and cascades to learning object names. Our home‐based study extends laboratory‐based theories to identify real‐world processes that support infant word learning. Frame‐by‐frame coding of 2‐hr video recordings of 32 mothers and their 18‐ to 23‐month‐old infants focused on infant manipulation and mother and infant naming of 245 unique objects. Objects manipulated by infants and/or named by mothers were more likely to appear in infants' vocabularies and spontaneous speech relative to nonmanipulated objects and objects that mothers did not name. Furthermore, the vocabularies of 5, 520 infants hosted on Wordbank revealed an early age of acquisition of words for objects that mothers named and infants manipulated. Infants actively build object–word mappings from everyday engagements with objects in the context of social interactions. Abstract :